1993
DOI: 10.1128/aac.37.7.1473
|View full text |Cite
|
Sign up to set email alerts
|

4-Guanidino-2,4-dideoxy-2,3-dehydro-N-acetylneuraminic acid is a highly effective inhibitor both of the sialidase (neuraminidase) and of growth of a wide range of influenza A and B viruses in vitro

Abstract: The sialidase (neuraminidase) inhibitor 4-guanidino-2,4-dideoxy-2,3-dehydro-N-acetylneuraminic acid (4-guanidino-Neu5Ac2en) has been examined for the ability to inhibit the growth of a wide range of influenza A The sialidase (neuraminidase, acylneuraminyl hydrolase, EC 3.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
175
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(182 citation statements)
references
References 25 publications
7
175
0
Order By: Relevance
“…The magnitude of the clinical benefit observed in this study appears to be at least as great as that in earlier trials of amantadine and rimantadine for acute febrile influenza A illness in adults. [17][18][19][20] In addition, as predicted by the results of in vitro studies, 8,9 tests in animal models, 8,10 and experimental studies in humans, 21 the antiviral spectrum and clinical effectiveness of zanamivir included influenza B virus infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the clinical benefit observed in this study appears to be at least as great as that in earlier trials of amantadine and rimantadine for acute febrile influenza A illness in adults. [17][18][19][20] In addition, as predicted by the results of in vitro studies, 8,9 tests in animal models, 8,10 and experimental studies in humans, 21 the antiviral spectrum and clinical effectiveness of zanamivir included influenza B virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Zanamivir inhibits a range of influenza A and B viruses in vitro. 8,9 Topically applied zanamivir is active in animal models of influenza, 3,8,10 although systemically administered drug has little antiviral activity. In adults experimentally inoculated with influenza A virus, prophylactic intranasal zanamivir was highly protective against infection and febrile illness.…”
Section: Conclusion In Adults With Influenzamentioning
confidence: 99%
“…To clarify the reason for the phenomenon observed in Italy91, further investigation on the HA gene of Italy91 would be necessary. However, since the human strains with reduced susceptibility to ZA in cell culture were shown to be sensitive to ZA in vivo [12,15], it is difficult to conclude that Italy91 is less susceptible to OC or ZA in vivo than the other EIVs from this limited study.…”
mentioning
confidence: 53%
“…Although the IC 50 s of OC and ZA for Italy91 were almost similar to those for the other EIVs examined in this study, the EC 50 s of both compounds for the virus were at least 75 times higher than those for the other EIVs. This phenomenon was observed in some human influenza A viruses [5,6,12,15]. Studies on human strains with reduced susceptibility to ZA in PRA showed that the resistance could be associated with mutations in the HA gene, and that a weaker affinity of the HA for the cellular receptors by HA mutations would allow release of virus from infected cells even in the presence of a NA inhibitor [5,6,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation